Evolution of B Chromosomes: From Dispensable Parasitic Chromosomes to Essential Genomic Players - Johnson Pokorná, Martina; Reifová, Radka (Frontiers in Genetics, 2021)
B chromosomes represent additional chromosomes found in many eukaryotic organisms. Their origin is not completely understood, but recent genomic studies suggest that they mostly arise through rearrangements and duplications from standard chromosomes. They can occur in a single or multiple copies in a cell and are usually present only in subset of individuals in the population. Because B chromosomes frequently show unstable inheritance, their maintenance in a population is often associated with meiotic drive or other mechanisms that increase the probability of their transmission to the next generation. For all these reasons, B chromosomes have been commonly considered to be nonessential, selfish, parasitic elements. Although it was originally believed that B chromosomes had little or no effect on an organism’s biology and fitness, a growing number of studies have shown that B chromosomes can play a significant role in processes such as sex determination, pathogenicity, or resistance to pathogens. In some cases, B chromosomes became an essential part of the genome, turning into new sex chromosomes, or germline-restricted chromosomes with important roles in the organism’s fertility. Here, we review such cases of ‘cellular domestication’ of B chromosomes and show that B chromosomes can be important genomic players with significant evolutionary impact.